(untitled) (World Bulletin of Management and Law, 2022)
The banking sector has developed over several centuries, to express a desire to invest the capitals in the hands of individuals, through large institutions, and to reinject money into economic projects, within the framework of the rule: indebtedness, between the bank and its dealers, which imposes a fixed interest rate on it. Islamic law forbids dealing with money in the form of: interest or usury. As a result of the embarrassment that some find themselves in when dealing with the traditional banking sector, Islamic banks have been developed, which operate according to the basis of partnership between the bank and its clients, in profit and loss, the Islamic bank enters the investment process as a partner in the business, not a party that gets the benefits of investing capital. The activity of the Islamic bank, and its operations, have contributed to pushing many individuals to employ their savings of money in the banking sector, which is considered a supportive activity for the banking sector.